Optimal ceftazidime/avibactam dosing exposure against KPC-producing Klebsiella pneumoniae. (29th August 2022) - Tam, Vincent H; Merlau, Paul R; Hudson, Cole S; Kline, Ellen G; Eales, Brianna M; Smith, James; Sofjan, Amelia K; Shields, Ryan K
Abstract: Objectives: Infections due to carbapenem-resistant Enterobacterales are considered urgent public health threats and often treated with a β-lactam/β-lactamase inhibitor combination. However, clinical treatment failure and resistance emergence have been attributed to inadequate dosing. We used a novel framework to provide insights of optimal dosing exposure of ceftazidime/avibactam. Methods: Seven clinical isolates of Klebsiella pneumoniae producing different KPC variants were examined. Ceftazidime susceptibility (MIC) was determined by broth dilution using escalating concentrations of avibactam. The observed MICs were characterized as response to avibactam concentrations using an inhibitory sigmoid E max model. Using the best-fit parameter values, % fT >MICi was estimated for various dosing regimens of ceftazidime/avibactam. A hollow-fibre infection model (HFIM) was subsequently used to ascertain the effectiveness of selected regimens over 120 h. The drug exposure threshold associated with bacterial suppression was identified by recursive partitioning. Results: In all scenarios, ceftazidime MIC reductions were well characterized with increasing avibactam concentrations. In HFIM, bacterial regrowth over time correlated with emergence of resistance. Overall, suppression of bacterial regrowth was associated with % fT >MICi   ≥   76.1% (100% versus 18.2%; P  <   0.001). Using our framework, the optimal drug exposure could be achieved with ceftazidime/avibactam 2.5 g every 12 h in 5 out of 7 isolates. Furthermore, ceftazidime/avibactam 2.5 g every 8 h can suppress an isolate deemed resistant based on conventional susceptibility testing method. Conclusions: An optimal drug exposure to suppress KPC-producing bacteria was identified. The novel framework is informative and may be used to guide optimal dosing of other β-lactam/β-lactamase inhibitor combinations. Further in vivo investigations are warranted.